Análisis de la propuesta de formación de la licenciatura en lenguas modernas, su coherencia con el currículo e intereses de los estudiantes (2016)
This project departs from the integral development of every future teacher’s profile, and it aims for establishing how the syllabus structure of the program of Modern Languages of the USB is coherent to its purpose. The impact and relevance of the areas which help future teachers to acquire the three areas of knowledge (the disciplinary knowledge, research knowledge and the educational knowledge) and its consistency with the future teachers’ integral proposed profile exposed on the program’s mission were inspected for such effect. The consultation at the documents and at the students’ and professors’ opinions allowed to determine that even though there is an imbalanced quantitative distribution of credits which provides the most to the disciplinary knowledge (studies of languages and of foreign cultures), the other two areas inherently acquire relevance and value in the hidden curriculum.